Alignment of Jean Piaget's Cognitive Development Theory in the Independent Curriculum: Christian Religious Education in Focus - Doni A; Yuprisila Dwi Hadassah (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
The problem background of this article discusses progress in human life and other organisms, from the beginning of life to changes in the life cycle. The term cognition Refers to mental processes in the human mind, important for understanding the world and interactions with the environment. Jean Piaget highlighted how children build understanding through stages of cognitive development. The Independent Curriculum and Christian religious education provide a relevant context for discussing education and holistic individual development. The method used in this article is library research, namely collecting data from various literature related to research. The stages of literature study include preparing equipment, making a bibliography, managing time, and reading and recording research materials. Data was collected through searching for sources from various media such as books, journals and previous research, with critical and in-depth explanations to support arguments and ideas. The result of this article is that cognitive development is influenced by different stages. Children think differently at each stage, for example from sensorimotor to formal operational. The Freedom to Learn curriculum can integrate Piaget's theory in Christian religious education with a focus on direct experience, critical questions, constructive activities, and stages of cognitive development. This helps students understand and process information better.